The effect of titanium anodization on the bond strength of 10-methacryloyloxydecyl dihydrogen phosphate (10-MDP) resin cement - Bömicke, Wolfgang; Rammelsberg, Peter; Spatola, Gianluca; Rues, Stefan (The international journal of prosthodontics, 2023)
Purpose: To examine the effects of anodization and different surface modifications of titanium on bond strength to 10-methacryloyloxydecyl dihydrogen phosphate (10-MDP) resin cement. Materials and Methods: Grade 5 titanium alloy disks (n = 160) were assigned to one of five prebonding surface treatment study groups (polished; polished and anodized; polished, etched, and anodized; sandblasted; sandblasted and anodized). Disks were adhesively bonded with 10-MDP resin cement (Panavia 21; bonding area: 3.3 mm in diameter) to composite resin cylinders. In each study group, tensile bond strength tests were conducted after 24 ± 1 hours and after 6 months (180 ± 2 days) of water storage (n = 16 specimens per water storage subgroup). Debonded specimens were stereomicroscopically analyzed to determine their fracture mode. Statistics included one-way and multifactorial ANOVA and Tukey post hoc tests (α = .05). Results: Anodization and water storage did not significantly (P ≥ .389) affect tensile bond strength. Although subgroups of polished samples had significantly (P ≤ .031) lower bond strengths (subgroup mean values: 20 to 26 MPa) than etched or sandblasted samples (subgroup mean values: 29 to 33 MPa), they nonetheless exceeded the empirical threshold of 10 MPa used as a criterion for clinical recommendation. The fracture mode of all test specimens was predominantly cohesive. Conclusions: Anodization of titanium surfaces can be performed without weakening the adhesion of 10-MDP–based resin cement to titanium.
Gesehen am 12.07.2024